Barrier laminate and method for producing same
Patent Information
- Application Number
- JP2024020007
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-28
- Filing Date
- 2024-02-14
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-05-21
Smart Images

Figure 0007652308000002 
Figure 0007652308000003 
Figure 0007652308000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a barrier laminate having a paper substrate as a support, and a method for producing the same. [Background technology]
[0002] Packaging materials with water vapor barrier properties or gas barrier properties (particularly oxygen barrier properties) imparted to a paper base material have traditionally been used in packaging foods, medical products, electronic components, etc. to prevent deterioration of the contents.
[0003] A common method for imparting water vapor barrier properties or gas barrier properties to a paper substrate is to laminate a synthetic resin film or metal foil with excellent gas barrier properties onto the paper substrate. However, materials in which a synthetic resin film or the like is laminated onto a paper substrate have problems in terms of the environment, since it is difficult to recycle the paper or synthetic resin after use.
[0004] Therefore, development of barrier materials that do not require lamination of synthetic resin films, etc. is underway. For example, Patent Document 1 discloses a paper barrier packaging material in which a water vapor barrier layer and a gas barrier layer are provided on a paper base material. The water vapor barrier layer contains 50 to 100% by weight of kaolin with an average particle size of 5 μm or more and an aspect ratio of 10 or more based on the total pigment, and the binder resin of the gas barrier layer is a polyvinyl alcohol resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5331265 Summary of the Invention [Problem to be solved by the invention]
[0006] When a barrier laminate having a water vapor barrier layer and a gas barrier layer on a paper base material is used as a packaging container, the barrier laminate is cut to a predetermined shape, and then folded into a bag-like or three-dimensional shape, and the edges are sealed by adhesion or the like to form a packaging container.
[0007] When the barrier laminate is folded, the water vapor barrier layer and the gas barrier layer on the paper base material are locally and significantly stretched at the folded portion, which may cause fine cracks to form in the water vapor barrier layer or the gas barrier layer, resulting in a deterioration in the water vapor barrier property or the gas barrier property of the packaging container.
[0008] The present invention has been made in view of the above-mentioned circumstances. That is, an object of the present invention is to provide a barrier laminate which is excellent in water vapor barrier property and gas barrier property and which is inhibited from being deteriorated in the water vapor barrier property and gas barrier property due to bending, and a method for producing the same. [Means for solving the problem]
[0009] The present inventors have investigated the formation of a protective layer on the water vapor barrier layer and the gas barrier layer in order to prevent deterioration in the water vapor barrier property and the gas barrier property due to folding of the barrier laminate. As a result, the present inventors have found that the provision of a protective layer is believed to make it difficult for local cracks to occur in the gas barrier layer and the water vapor barrier layer below the protective layer when the barrier laminate is folded, and as a result, deterioration in the water vapor barrier property and the gas barrier property, particularly deterioration in the gas barrier property, is prevented.
[0010] The present invention has been completed based on these findings. That is, the present invention has the following configuration. (1) A barrier laminate having a water vapor barrier layer, a gas barrier layer and a protective layer, in this order, on at least one surface of a paper base material, characterized in that the water vapor barrier layer contains a water-suspendable polymer, a layered inorganic compound and a cationic resin, the gas barrier layer contains a water-soluble polymer, and the protective layer contains at least one of a water-soluble polymer and a water-suspendable polymer. (2) Water vapor permeability is 20g / ( m 2 ·day ) The oxygen permeability is 10cc / ( m 2 ·day·atm ) The barrier laminate according to the above (1), which is: (3) The barrier laminate according to (1) or (2), wherein the water vapor barrier layer, the gas barrier layer and the protective layer are simultaneously multi-coated layers. Here, the term "simultaneous multi-layer coating layer" refers to a multi-layer coating layer formed by a simultaneous multi-layer coating method. It is difficult to clearly distinguish a simultaneous multi-layer coating layer from a multi-layer coating layer formed sequentially based on its appearance. In other words, it is difficult to directly identify a simultaneous multi-layer coating layer by its structure or properties, distinguishing it from a multi-layer coating layer formed sequentially.
[0011] (4) The barrier laminate according to any one of (1) to (3) above, wherein the water-soluble polymer is polyvinyl alcohol or modified polyvinyl alcohol. (5) The barrier laminate according to any one of (1) to (4), wherein the water-dispersible polymer contains at least one of an ethylene-acrylic copolymer, a styrene-butadiene copolymer, a styrene-acrylic copolymer, and a biodegradable resin. (6) The barrier laminate according to (5) above, wherein the biodegradable resin is at least one of polybutylene succinate, polybutylene succinate adipate, polylactic acid, polybutylene adipate terephthalate, and a 3-hydroxybutanoic acid / 3-hydroxyhexanoic acid copolymer.
[0012] (7) The barrier laminate according to any one of (1) to (6) above, wherein the layered inorganic compound has an aspect ratio of 80 or more and a thickness of 120 nm or less. (8) The barrier laminate according to any one of (1) to (7) above, wherein the layered inorganic compound is at least one selected from the group consisting of mica, bentonite, kaolin, and talc. (9) The barrier laminate according to any one of (1) to (8) above, wherein the cationic resin is at least one selected from the group consisting of polyamines, modified polyamides, modified polyamidoamines, polyamide epichlorohydrin, and polyethyleneimines.
[0013] (10) The paper base material has a basis weight of 20 to 500 g / m 2 and the density is 0.5 to 1.2 g / cm 3 The barrier laminate according to any one of (1) to (9) above, having an Oken smoothness of 5 seconds or more. (11) A method for producing the barrier laminate according to any one of (1) to (10) above, characterized in that the water vapor barrier layer, the gas barrier layer and the protective layer are formed by a simultaneous multi-layer coating method. (12) The method for producing a barrier laminate according to (11) above, wherein the coating method of the simultaneous multi-layer coating method is a simultaneous multi-layer slide curtain method or a simultaneous multi-layer slide bead method. Effect of the Invention
[0014] According to the present invention, there are provided a barrier laminate excellent in water vapor barrier property and gas barrier property and suppressing deterioration of the water vapor barrier property and the gas barrier property due to bending, and a method for producing the same. [Brief description of the drawings]
[0015] [Figure 1] 1 is a schematic cross-sectional view showing a layer structure of a barrier laminate according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing the layer structure of a barrier laminate according to a second embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the embodiments of the present invention will be described in detail. The following description of the constituent elements may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "~" means a range including the numerical values before and after "~" as the lower and upper limits.
[0017] The barrier laminate of this embodiment has a water vapor barrier layer, a gas barrier layer and a protective layer in this order on at least one surface of a paper substrate. The water vapor barrier layer, the gas barrier layer and the protective layer may be provided on only one surface of the paper substrate, or the water vapor barrier layer, the gas barrier layer and the protective layer may be provided on both surfaces of the paper substrate. Each layer constituting the barrier laminate of this embodiment will be described below.
[0018] [Paper base material] The paper base material used in the present embodiment is not particularly limited as long as it is a commonly used paper containing plant-derived wood pulp as the main component. Specific examples include bleached or unbleached kraft paper, fine paper, paperboard, liner paper, coated paper, one-sided gloss paper, glassine paper, graphene paper, etc. The paper base material is preferably a paper containing pulp as the main component, which is easily dispersible in water by mechanical disintegration.
[0019] From the viewpoint of improving the barrier property, the disintegrated freeness (freeness) of the paper base material measured in accordance with JIS P8121:2012 is preferably 800 mL or less, more preferably 550 mL or less. Here, the disintegrated freeness refers to the Canadian standard freeness measured in accordance with JIS P8121:2012 on the pulp obtained by disintegrating the paper after papermaking in accordance with JIS P8220-1:2012. A known method can be used as a method for beating the pulp to adjust the disintegrated freeness.
[0020] The sizing degree of the paper base material is not particularly limited, but from the viewpoint of improving the barrier property, it is preferable that the Stockigt sizing degree according to JIS P 8122:2004 is 1 second or more. The sizing degree of the paper base material can be controlled by the type and content of the internal sizing agent such as rosin-based, alkyl ketene dimer-based, alkenyl succinic anhydride-based, styrene-acrylic, higher fatty acid-based, petroleum resin-based, etc., the type of pulp, smoothing treatment, etc. The content of the internal sizing agent is not particularly limited, but is preferably in the range of about 0 to 3 parts by mass per 100 parts by mass of the pulp of the paper base material.
[0021] The paper base material may contain known internal additives, such as fillers such as titanium dioxide, kaolin, talc, and calcium carbonate, paper strength agents, retention aids, pH adjusters, drainage improvers, water resistance agents, softeners, antistatic agents, defoamers, slime control agents, dyes and pigments, and the like.
[0022] In the papermaking of the paper base material, a known wet papermaking machine (e.g., a Fourdrinier papermaking machine, a gap former type papermaking machine, a cylinder papermaking machine, a short wire papermaking machine, etc.) is appropriately selected and used. The paper layer formed by the papermaking machine is transported on a felt and dried in a dryer. A multi-stage cylinder dryer may be used as a pre-dryer before drying with the dryer.
[0023] The paper substrate thus obtained may be surface-treated with a calendar to make the thickness and profile uniform. A known calendaring machine may be appropriately selected and used for the calendaring.
[0024] The basis weight of the paper base material is not particularly limited, but is preferably 20 to 500 g / m 2 It is preferable that the thickness is 30 to 400 g / m 2 The basis weight of the paper base material is measured in accordance with JIS P 8124:2011. From the viewpoint of moldability, the density of the paper base material is 0.5 to 1.2 g / cm 3and preferably 0.6 to 1.0 g / cm 3 The density of the paper base material is calculated from the thickness of the paper base material measured in accordance with JIS P 8118:2014 and the above basis weight. From the viewpoint of film-forming properties of the coating layer, the paper substrate preferably has an Oken smoothness of 5 seconds or more, more preferably 10 to 1000 seconds. From the viewpoint of printability, the paper substrate preferably has a 75° gloss of 5% or more, more preferably 10 to 70%. The Oken smoothness is measured in accordance with JIS P 8155:2010. The gloss is measured in accordance with JIS P 8142:2005.
[0025] [Water vapor barrier layer] The water vapor barrier layer is a layer having a function of preventing the permeation of water vapor, and contains a water-suspendable polymer, a layered inorganic compound, and a cationic resin.
[0026] (Layered inorganic compounds) The layered inorganic compound has a flat shape. When a mixed solution of the layered inorganic compound, a water-suspendable polymer, and a cationic resin is prepared and applied onto a paper substrate, a water vapor barrier layer is formed. In the water vapor barrier layer, the flat layered inorganic compound is arranged in a state of being stacked almost parallel to the plane (surface) of the paper substrate. In this way, the area of the region where the layered inorganic compound is not present in the plane direction of the paper substrate is reduced, so that the permeation of water vapor is suppressed. In addition, in the thickness direction of the paper substrate, the flat layered inorganic compound is arranged in a state of being parallel to the plane of the paper substrate, so that the water vapor in the water vapor barrier layer permeates while bypassing the layered inorganic compound, and the permeation of water vapor is suppressed by the maze effect. As a result, the water vapor barrier layer can exhibit excellent water vapor barrier properties.
[0027] The thickness of the layered inorganic compound is preferably 120 nm or less. The thickness of the layered inorganic compound is more preferably 100 nm or less, further preferably 50 nm or less, and particularly preferably 20 nm or less. The smaller the average thickness of the layered inorganic compound, the greater the number of laminations of the layered inorganic compound in the water vapor barrier layer, and therefore the higher the water vapor barrier property can be exhibited. Here, the thickness of the layered inorganic compound in the state of being contained in the water vapor barrier layer is obtained as follows. First, a magnified photograph is taken of the cross section of the water vapor barrier layer using an electron microscope. At this time, the magnification is set so that about 20 to 30 pieces of the layered inorganic compound are contained in the screen. Next, the thickness of each layered inorganic compound in the screen is measured. Then, the average value of the obtained thicknesses is calculated to be the thickness of the layered inorganic compound.
[0028] The length of the layered inorganic compound is preferably 1 μm to 100 μm. When the length is 1 μm or more, the layered inorganic compound is easily arranged parallel to the paper base material. When the length is 100 μm or less, there is little concern that a part of the layered inorganic compound protrudes from the water vapor barrier layer. The length is more preferably 2 to 60 μm, and even more preferably 3 to 30 μm. Here, the length of the layered inorganic compound in the state of being contained in the water vapor barrier layer is obtained as follows. First, an enlarged photograph is taken of the cross section of the water vapor barrier layer using an electron microscope. At this time, the magnification is set so that about 20 to 30 pieces of the layered inorganic compound are contained in the screen. Next, the length of each layered inorganic compound in the screen is measured. Then, the average value of the obtained lengths is calculated to be the length of the layered inorganic compound. The length of the layered inorganic compound may also be expressed as a particle diameter.
[0029] The aspect ratio of the layered inorganic compound is preferably 80 or more. When the aspect ratio is 80 or more, it is possible to achieve a predetermined water vapor barrier property. The aspect ratio of the layered inorganic compound is more preferably 100 or more, more preferably 200 or more, particularly preferably 300 or more, and most preferably 500 or more. The larger the aspect ratio, the more the water vapor permeation is suppressed and the water vapor barrier property is improved. In addition, the larger the aspect ratio, the less the amount of the layered inorganic compound added can be. The upper limit of the aspect ratio is not particularly limited, and is preferably about 10,000 or less from the viewpoint of the viscosity of the coating liquid. Here, the aspect ratio is a value obtained by taking an enlarged photograph of the cross section of the water vapor barrier layer using an electron microscope, and dividing the average length of the layered inorganic compound obtained by the above-mentioned method by its average thickness.
[0030] Specific examples of layered inorganic compounds include micas such as mica and brittle mica, synthetic mica (e.g., swelling mica and non-swelling mica), bentonite, kaolinite (kaolin mineral), pyrophyllite, talc, smectite, vermiculite, chlorite, septe chlorite, serpentine, stilpnomelane, and montmorillonite.
[0031] Among the layered inorganic compounds, at least one selected from mica, bentonite, kaolin, and talc is particularly preferred from the viewpoint of improving the barrier property. Examples of mica include synthetic mica, white mica (muscovite), sericite, phloxopite, biotite, fluorine phlogopite (artificial mica), red mica, soda mica, vanadium mica, illite, chin mica, paragonite, and brittle mica. Examples of bentonite include montmorillonite. Kaolin is a clay formed by weathering rocks containing feldspar, and is mainly composed of kaolinite. Talc is a mineral composed of magnesium hydroxide and silicate, and is also called talc.
[0032] The content of the layered inorganic compound is preferably 80 mass% or less, more preferably 70 mass% or less, even more preferably 30 mass% or less, particularly preferably 20 mass% or less, and most preferably 10 mass% or less, based on the total solid content of the water vapor barrier layer. On the other hand, the content of the layered inorganic compound is preferably 1 mass% or more, more preferably 2 mass% or more. By increasing the aspect ratio of the layered inorganic compound and reducing the thickness, the content of the layered inorganic compound can be reduced, and the falling off of the layered inorganic compound from the water vapor barrier layer can be suppressed.
[0033] The content of the layered inorganic compound is preferably 0.1 to 800 parts by mass relative to 100 parts by mass of the water-suspendable polymer (binder) of the water vapor barrier layer. The content of the layered inorganic compound is preferably 0.3 to 400 parts by mass relative to 100 parts by mass of the water-suspendable polymer (binder) of the water vapor barrier layer, more preferably 1 to 200 parts by mass, even more preferably 3 to 100 parts by mass, particularly preferably 5 to 50 parts by mass, and most preferably 7 to 20 parts by mass. When the content of the layered inorganic compound is 0.1 parts by mass or more relative to 100 parts by mass of the water-suspendable polymer (binder) of the water vapor barrier layer, the water vapor barrier property is easily exhibited. In addition, when the content of the layered inorganic compound is 800 parts by mass or less relative to 100 parts by mass of the water-suspendable polymer (binder) of the water vapor barrier layer, a part of the layered inorganic compound is unlikely to be exposed from the layer surface, so that the water vapor barrier property is unlikely to decrease. Furthermore, when the content of the layered inorganic compound is 800 parts by mass or less relative to 100 parts by mass of the water-suspendable polymer of the water vapor barrier layer, the coatability of the gas barrier layer is good and a uniform gas barrier layer is formed, resulting in good gas barrier properties.
[0034] (cationic resin) The present inventors have found that the water vapor barrier property is greatly improved by adding a cationic resin to a water vapor barrier layer containing a layered inorganic compound.
[0035] The reason why the water vapor barrier property is greatly improved by adding a cationic resin is considered to be as follows. It is known that layered inorganic compounds have a so-called house-of-cards structure in which the flat surfaces of the flat plate-like form are easily charged with anionic charge and the edges are easily charged with cationic charge, so that the layered inorganic compounds are three-dimensionally aggregated together. Due to this house-of-cards structure, the viscosity of the aqueous dispersion of the layered inorganic compound becomes very high. On the other hand, the house-of-cards structure is easily broken when force is applied by stirring or the like, so that the aqueous dispersion of the layered inorganic compound exhibits thixotropy.
[0036] When an appropriate cationic resin is added to an aqueous dispersion of a layered inorganic compound, the cationic resin is adsorbed to the anionic planar portion of the layered inorganic compound, destroying the house-of-cards structure. As a result, the layered inorganic compound is prevented from aggregating three-dimensionally, and the flat-plate-like layered inorganic compound is easily laminated parallel to the plane of the paper base material, which is believed to lead to improved water vapor barrier properties.
[0037] Specific examples of cationic resins include polyamines, modified polyamides, modified polyamidoamines, polyamidoepichlorohydrin, polyethyleneimine, polyalkylenepolyamines, polyamide compounds, polyamidoamine-epihalohydrin or formaldehyde condensation reaction products, polyamine-epihalohydrin or formaldehyde condensation reaction products, polyamidepolyurea-epihalohydrin or formaldehyde condensation reaction products, polyaminepolyurea-epihalohydrin or formaldehyde condensation reaction products, polyamidoaminepolyurea-epihalohydrin or formaldehyde condensation reaction products, polyamidepolyurea compounds, polyaminepolyurea compounds, polyamidoaminepolyurea compounds and polyamidoamine compounds, polyvinylpyridine, amino-modified acrylamide compounds, polyvinylamine, and polydiallyldimethylammonium chloride. Among these, at least one selected from polyamine, modified polyamide, modified polyamidoamine, polyamide epichlorohydrin, and polyethyleneimine is preferred.
[0038] The cationic resin preferably has a surface charge of 0.1 to 10 meq / g, more preferably 0.1 to 5.0 meq / g. When the surface charge of the cationic resin is within the above range, it is possible to destroy the house-of-cards structure and to appropriately coexist with the anionic binder described below.
[0039] The surface charge of the cationic resin is measured by the method described below. First, a sample polymer is dissolved in water to obtain a solution with a polymer concentration of 1 ppm. 0.001N sodium polyethylene sulfonate is dropped into the solution using a charge analyzer Mutek PCD-04 (manufactured by BTG) to measure the amount of charge.
[0040] The content of the cationic resin in the water vapor barrier layer may be appropriately determined depending on the types of layered inorganic compound and water-suspendable polymer used in the water vapor barrier layer, but from the viewpoint of improving the barrier property, the content is preferably 1 to 300 parts by mass, more preferably 1 to 250 parts by mass, even more preferably 10 to 150 parts by mass, particularly preferably 20 to 150 parts by mass, and most preferably 40 to 100 parts by mass, relative to 100 parts by mass of the layered inorganic compound.
[0041] The content of the cationic resin is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 15 parts by mass, and even more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the water-suspendable polymer (binder) of the water vapor barrier layer.
[0042] (Water-suspended polymer) A water-suspendable polymer is a polymer that can be suspended in water, and when forming a coating film, it is easy to prepare a coating liquid using water as a solvent. Since a water-suspendable polymer functions as a binder in forming a coating film, a coating film containing a layered inorganic compound or the like can be formed on a paper substrate. The polymer that forms the backbone of the water-suspendable polymer preferably contains at least one of an ethylene-acrylic copolymer, a styrene-butadiene copolymer, a styrene-acrylic copolymer, and a biodegradable resin.
[0043] The following will explain the structure of ethylene-acrylic copolymers, which are representative water-dispersible polymers. Examples of acrylic monomers that make up ethylene-acrylic copolymers include (meth)acrylic acid and its alkyl esters. The number of carbon atoms in the alkyl group of the ester moiety of the (meth)acrylic acid alkyl ester is preferably 1 or more and 8 or less, more preferably 1 or more and 6 or less, and even more preferably 1 or more and 4 or less. Here, (meth)acrylic acid means methacrylic acid and acrylic acid. The acrylic monomer constituting the ethylene-acrylic copolymer may be one type, or two or more types may be used in combination.
[0044] The ethylene-acrylic copolymer is a copolymer obtained by emulsion polymerization of ethylene and the above-mentioned acrylic monomer. As the acrylic monomer, acrylic acid, methacrylic acid, etc. are suitable. As the ethylene-acrylic copolymer, it is preferable to use at least one of ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-ethyl methacrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-butyl methacrylate copolymer. The copolymer may contain a small amount of monomers composed of other compounds copolymerizable with ethylene and the acrylic monomer.
[0045] As a specific example of an ethylene-acrylic copolymer, for example, an aqueous dispersion of an ethylene-acrylic acid copolymer ammonium salt is commercially available as ZAIXXEN (registered trademark) AC (copolymerization ratio of acrylic acid: 20 mol%, manufactured by Sumitomo Seika Chemicals Co., Ltd.), and can be easily obtained and used.
[0046] The ethylene-acrylic copolymer preferably has an acrylic monomer unit content of 1 to 50 mol%. When the acrylic monomer unit content is within this range, the ethylene-acrylic copolymer has excellent dispersibility, has a melting temperature of 60 to 120°C, and exhibits good heat sealability, making it suitable as a water-suspendable polymer for the protective layer described below. The acrylic monomer unit content in the ethylene-acrylic copolymer is more preferably 10 to 30 mol%.
[0047] The weight average molecular weight of the ethylene-acrylic copolymer is preferably from 10,000 to 10,000,000, and more preferably from 100,000 to 5,000,000, from the viewpoints of the viscosity of the coating liquid and the strength of the coating film.
[0048] The content of the ethylene-acrylic copolymer is not particularly limited, but is preferably 20 mass % or more of the total solid content of the water vapor barrier layer, more preferably 50 mass % or more, even more preferably 60 mass % or more, particularly preferably 70 mass % or more, and most preferably 80 mass % or more.
[0049] (Styrene-butadiene copolymer) Styrene-butadiene copolymers are copolymers obtained by emulsion polymerization of monomers consisting of styrene compounds such as styrene, α-methylstyrene, vinyltoluene, pt-butylstyrene, and chlorostyrene, butadiene compounds such as 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene, and other compounds that can be copolymerized with these. Styrene is the preferred styrene compound, and 1,3-butadiene is the preferred butadiene compound.
[0050] (styrene-acrylic copolymer) Styrene-acrylic copolymers are copolymers obtained by emulsion polymerization of monomers consisting of styrene compounds such as styrene, α-methylstyrene, vinyltoluene, pt-butylstyrene, and chlorostyrene, acrylic compounds such as acrylic acid, methacrylic acid, (meth)acrylic acid esters, (meth)acrylamidopropanesulfonic acid, and (meth)acrylic acid sulfoalkyl sodium salts (alkyl groups with 2 to 3 carbon atoms), and other compounds that can be copolymerized with these. Styrene is the preferred styrene compound, and acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters are the preferred acrylic compounds.
[0051] (biodegradable resin) Specific examples of biodegradable resins are not particularly limited, and include, for example, polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), 3-hydroxybutanoic acid-3-hydroxyhexanoic acid copolymer (PHBH), etc. Among these, PBS and PLA are preferred, and PLA is more preferred. Packaging materials using paper substrates have the advantage of reducing the environmental load compared to packaging materials using thermoplastic resins, but the environmental load can be further reduced by using a biodegradable resin as the water-suspendable polymer of the water vapor barrier layer.
[0052] The water-suspendable polymer (binder) in the water vapor barrier layer is preferably anionic. When the binder is anionic, the water vapor barrier property is further improved. As described above, the planar portion of the layered inorganic compound is anionic, but when the cationic resin is adsorbed, the surface becomes cationic. Therefore, the affinity with the anionic binder is increased. When the skeleton of the water-dispersible polymer does not have an anionic group, it is preferable to introduce an acid group by copolymerizing with a monomer having an acid group such as a carboxy group.
[0053] The weight average molecular weight of the water-suspendable polymer is preferably from 10,000 to 10,000,000, and more preferably from 100,000 to 5,000,000, from the viewpoints of the viscosity of the coating liquid and the strength of the coating film. The content ratio of the water-suspendable polymer in the water vapor barrier layer is not particularly limited, but is preferably 20 mass % or more of the total solid content of the water vapor barrier layer, more preferably 50 mass % or more, even more preferably 60 mass % or more, particularly preferably 70 mass % or more, and most preferably 80 mass % or more.
[0054] In addition to the water-suspendable polymer, layered inorganic compound, and cationic resin, dispersants, surfactants, defoamers, wetting agents, dyes, color adjusters, thickeners, and the like can be appropriately added to the water vapor barrier layer as necessary.
[0055] The thickness of the water vapor barrier layer is preferably 1 to 30 μm, more preferably 3 to 20 μm. The coating amount of the water vapor barrier layer is 1 to 30 g / m2 in terms of solid content. 2 It is preferable that the thickness is 3 to 20 g / m 2 It is more preferable that:
[0056] [Gas barrier layer] The gas barrier layer is a layer that has a function of mainly preventing the permeation of oxygen gas, and contains a water-soluble polymer.
[0057] (Water-soluble polymer) Examples of water-soluble polymers include polyvinyl alcohol, modified polyvinyl alcohol, starch and its derivatives, cellulose derivatives, polyvinylpyrrolidone, urethane resins, polyacrylic acid and its salts, casein, and polyethyleneimine.
[0058] Among these, polyvinyl alcohol or modified polyvinyl alcohol is preferred because it has better gas barrier properties. Examples of polyvinyl alcohol include fully saponified or partially saponified polyvinyl alcohol. Examples of modified polyvinyl alcohol include ethylene-modified polyvinyl alcohol, carboxy-modified polyvinyl alcohol, silicon-modified polyvinyl alcohol, acetoacetyl-modified polyvinyl alcohol, diacetone-modified polyvinyl alcohol, etc.
[0059] The content of the water-soluble polymer is preferably 50 to 100 mass % of the total solid content of the gas barrier layer, and more preferably 70 to 100 mass %.
[0060] The gas barrier layer may contain the layered inorganic compound as described above, similarly to the water vapor barrier layer. When the layered inorganic compound is contained in the gas barrier layer, the content of the layered inorganic compound is not particularly limited, but is preferably 0.1 to 200 parts by mass, more preferably 0.5 to 150 parts by mass, more preferably about 1 to 40 parts by mass, particularly preferably 5 to 30 parts by mass, and most preferably 10 to 25 parts by mass, relative to 100 parts by mass of the water-soluble polymer of the gas barrier layer. From the viewpoint of improving the barrier property, the layered inorganic compound is preferably at least one selected from mica, bentonite, kaolin, and talc. The layered inorganic compound contained in the gas barrier layer may be the same type as the layered inorganic compound contained in the water vapor barrier layer, or may be a different type.
[0061] In addition to the water-soluble polymer and the layered inorganic compound, the gas barrier layer may contain, as necessary, appropriate additives such as pigments, dispersants, surfactants, defoamers, wetting agents, dyes, color adjusters, thickeners, etc. The gas barrier layer may contain a layered inorganic compound appropriately selected from those usable in the water vapor barrier layer.
[0062] The thickness of the gas barrier layer is preferably 0.1 to 10 μm, more preferably 0.5 to 5 μm. The coating amount of the gas barrier layer is 0.1 to 10 g / m2 in terms of solid content.2 It is preferable that the thickness is 0.5 to 5 g / m 2 It is more preferable that:
[0063] [Protective layer] The protective layer is a layer formed on the gas barrier layer, and contains at least one of a water-soluble polymer and a water-suspendable polymer.
[0064] When the barrier laminate is used as a packaging container, it is cut into a predetermined shape, then folded into a bag or three-dimensional shape, and the edges are sealed by adhesion, etc. In this case, the water vapor barrier layer and gas barrier layer on the paper base material are locally significantly stretched at the folded parts of the barrier laminate, and there is a risk of fine cracks, etc. occurring in the water vapor barrier layer or gas barrier layer.
[0065] Therefore, the present inventors have considered forming a protective layer on the gas barrier layer. When a protective layer is present on the gas barrier layer, the gas barrier layer and the protective layer are in close contact with each other, and therefore the gas barrier layer and the protective layer are deformed as one unit when the gas barrier layer is folded, making it difficult for fine cracks to occur on the surface of the gas barrier layer. As a result, it is possible to suppress the deterioration of the water vapor barrier property and the gas barrier property, particularly the deterioration of the gas barrier property, caused by folding the barrier laminate.
[0066] The protective layer contains either a water-soluble polymer or a water-suspendable polymer. The contents of the water-soluble polymer and the water-suspendable polymer are as described above. When the protective layer is made of a water-soluble polymer, the protective layer is the same type of layer as the gas barrier layer. When the protective layer is made of a water-suspendable polymer, the protective layer is the same type of layer as the water vapor barrier layer. In addition to the two layers of the water vapor barrier layer and the gas barrier layer, a third layer is present, so that the performance of the water vapor barrier property and the gas barrier property can be improved. Furthermore, if a resin having excellent heat sealability among the water-soluble polymers or the water-suspendable polymers is used as the protective layer, it is possible to impart heat sealability to the barrier laminate. Furthermore, if a biodegradable resin is used as the protective layer, it is possible to impart biodegradability to the protective layer. Specific examples of the biodegradable resin are as described above.
[0067] The thickness of the protective layer is preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm. The coating amount of the protective layer is 0.1 to 10 g / m2 in terms of solid content. 2 It is preferable that the thickness is 0.5 to 5 g / m 2 It is more preferable that:
[0068] [Barrier laminate] 1 is a schematic cross-sectional view showing the layer structure of a barrier laminate 10 according to a first embodiment of the present invention. A water vapor barrier layer 2, a gas barrier layer 3, and a protective layer 4A are present in this order on one surface of a paper substrate 1. In the barrier laminate 10 of the first embodiment, the protective layer 4A is formed from a water-suspendable polymer having heat-sealability.
[0069] 2 is a schematic cross-sectional view showing the layer structure of a barrier laminate 20 according to a second embodiment of the present invention. A water vapor barrier layer 2, a gas barrier layer 3, and a protective layer 4B are present in this order on one surface of a paper substrate 1. In the barrier laminate 20 of the second embodiment, the protective layer 4B is formed from a water-soluble polymer.
[0070] The barrier laminate of the present embodiment has excellent water vapor barrier properties and gas barrier properties. Specifically, the water vapor barrier properties are those having a water vapor permeability of 20 g / (m 2 ·day) or less, and 10g / (m 2 It is more preferable that the time is 100-240 s or less. Gas barrier properties are specifically defined as an oxygen permeability of 10 cc / (m 2 ·day·atm) or less, and ( m 2 ·day·atm ) More preferably, it is 3cc / ( m 2 ·day·atm ) It is even more preferable that: The barrier laminate of this embodiment is inhibited from decreasing in water vapor barrier property and gas barrier property due to folding, and preferably has the above-mentioned water vapor permeability and oxygen permeability even after folding.
[0071] [Method of manufacturing the barrier laminate] The barrier laminate of this embodiment has three coating layers with excellent barrier properties on a paper substrate. When forming multiple coating layers such as a water vapor barrier layer and a gas barrier layer on a paper substrate, conventionally, a water vapor barrier layer forming coating liquid is applied to the paper substrate, dried, and then a gas barrier layer forming coating liquid is applied and dried. When multiple coating layers are formed on a paper substrate, if a method of forming coating layers sequentially is adopted, when a gas barrier layer forming coating liquid is applied on a water vapor barrier layer and dried, volatile components such as moisture present in the gas barrier layer forming coating liquid cannot escape from the water vapor barrier layer side below. Therefore, the volatile components expand inside the gas barrier layer, causing so-called blisters, cracks, and poor drying. When blisters or cracks occur, not only does the barrier property decrease, but the smoothness of the surface of the coating layer is impaired, leading to a decrease in marketability.
[0072] The present inventors have focused on a simultaneous multi-layer coating method as a method for forming coating layers with a multi-layer structure. The simultaneous multi-layer coating method is a method in which multiple types of coating liquids are ejected from separate slit-shaped nozzles to form a liquid laminate, which is then coated onto a paper substrate to simultaneously form multiple coating films. For example, see JP-T-2004-527669 and JP-T-2012-505321.
[0073] The present inventors have found that the occurrence of blisters can be effectively suppressed by adopting a simultaneous multi-layer coating method. In this embodiment, the "simultaneous multi-layer coating layer" refers to a water vapor barrier layer, a gas barrier layer, and a protective layer formed using the simultaneous multi-layer coating method. In the simultaneous multi-layer coating method, multiple undried coating films are formed and dried at the same time, so that it is assumed that volatile matter easily disperses from the inside to the outside, making it difficult for blisters and cracks to occur. In addition, the simultaneous multi-layer coating method is also effective in suppressing the occurrence of local cracks in the coating film when folded.
[0074] Furthermore, since multiple coating films are formed simultaneously, the occurrence of pinholes is suppressed, which is effective in improving the quality of the barrier laminate. In addition, since multiple coating films are formed simultaneously, the productivity is greatly improved compared to the conventional sequential coating method.
[0075] The coating methods for the simultaneous multi-layer coating method include the simultaneous multi-layer slide curtain method and the simultaneous multi-layer slide bead method, and either method may be used. The simultaneous multi-layer slide curtain method is a method in which a coating film is made to flow in a curtain shape from a slide die with multiple slits and coated onto a substrate. The simultaneous multi-layer slide bead method is a method in which the coating liquid flowing down from a slide die with multiple slits forms a liquid bridge part (bead part) between the tip of the die and the traveling substrate, and coating is performed through the bead part.
[0076] The solvent for the coating liquid is not particularly limited, and may be water or an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, or toluene.
[0077] As a coating facility for applying a coating liquid to a paper substrate by the simultaneous multi-layer coating method, a coating device of a simultaneous multi-layer slide curtain type or a simultaneous multi-layer slide bead type capable of performing the simultaneous multi-layer coating method is used.
[0078] The drying equipment for drying the coating layer is not particularly limited, and known equipment can be used. Examples of the drying equipment include a hot air dryer, an infrared dryer, a gas burner, and a hot plate.
[0079] Taking advantage of the excellent water vapor barrier property and gas barrier property described above, the barrier laminate of this embodiment can be suitably used as a packaging material for foods, medical products, electronic components, etc. In addition, since the barrier laminate of this embodiment has resistance to fold cracking, it can be suitably used as a flexible packaging material. EXAMPLES
[0080] The barrier laminate of the present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. In the examples and comparative examples, "parts" and "%" respectively mean "parts by mass" and "% by mass" unless otherwise specified.
[0081] The raw materials used in the examples and comparative examples are as follows. (1)Paper base material Bleached kraft paper: grammage 50g / m 2 , thickness 60μm, disintegration freeness 520mL, Stockigt size degree 15 seconds, smoothness 70 seconds (2) Layered inorganic compounds Synthetic mica: Swellable mica, particle size 6.3 μm, aspect ratio approx. 1000, thickness approx. 5 nm, product name: NTO-05, manufactured by Topy Industries, Inc., aqueous dispersion with 6% solid content Kaolin: Engineered kaolin, particle size 10 μm, aspect ratio approximately 100, thickness approximately 100 nm, product name: Varisurf HX, manufactured by Imerys (3) Cationic resin Modified polyamide resin: solid content 53%, product name: SPI203(50)H, manufactured by Taoka Chemical Co., Ltd., surface charge 0.4meq / g (4) Water-suspended polymer Ethylene-acrylic copolymer: Self-emulsifying ethylene-acrylic acid copolymer emulsion, solid content 29.2%, product name: ZAIKXEN AC, manufactured by Sumitomo Seika Chemicals Co., Ltd. Polylactic acid: Aqueous suspension of polylactic acid, Randy PL-3000, manufactured by Miyoshi Oil Co., Ltd. (5) Water-soluble polymer Modified polyvinyl alcohol: Ethylene-modified polyvinyl alcohol, fully saponified type, product name: Exeval AQ-4104, manufactured by Kuraray Co., Ltd.
[0082] Example 1 34.3 parts of self-emulsifying ethylene-acrylic acid copolymer emulsion was added to 19.7 parts of an aqueous dispersion of synthetic mica while stirring, and the mixture was stirred. 1.7 parts of modified polyamide resin was added to the mixture, and the mixture was stirred. Next, 0.1 parts of 25% aqueous ammonia solution was added, and the mixture was stirred. Further, dilution water was added to make the solids concentration 20%, and the coating liquid for the water vapor barrier layer was prepared. In addition, an aqueous solution of modified polyvinyl alcohol with a solids concentration of 10% was prepared, and the coating liquid for the gas barrier layer was prepared. In addition, an aqueous solution of modified polyvinyl alcohol with a solids concentration of 10% was prepared, and the coating liquid for the protective layer was prepared.
[0083] The coating amount of the water vapor barrier layer coating solution (after drying) is 6 g / m 2 The coating amount (after drying) of the gas barrier layer coating solution on the water vapor barrier layer was 3.0 g / m 2 Furthermore, the coating amount (after drying) of the protective layer coating solution on the gas barrier layer was 3.0 g / m 2 Three layers were simultaneously coated on bleached kraft paper so that the thickness of the coating was 30 μm. A multi-layer slide curtain coater for experiments was used for the simultaneous coating. The resulting product was then dried in a hot air dryer at 120°C for 3 minutes to obtain a barrier laminate.
[0084] Example 2 A barrier laminate was obtained in the same manner as in Example 1, except that the protective layer coating liquid was changed to a self-emulsifying ethylene-acrylic acid copolymer emulsion.
[0085] Example 3 A barrier laminate was obtained in the same manner as in Example 1, except that the protective layer coating liquid was changed to an aqueous suspension of polylactic acid.
[0086] Example 4 A coating liquid for a gas barrier layer was prepared by adding 33 parts of an aqueous dispersion of synthetic mica to 100 parts of an aqueous solution of modified polyvinyl alcohol with a solid content of 10%. A barrier laminate was obtained in the same manner as in Example 1, except that the coating liquid for a gas barrier layer was used.
[0087] Example 5 Kaolin was dispersed in water to obtain a kaolin aqueous dispersion with a solid content of 55%. 47.8 parts of the kaolin aqueous dispersion was added to 45 parts of a self-emulsifying ethylene-acrylic acid copolymer emulsion while stirring, and the mixture was stirred. 1 part of a modified polyamide resin was added thereto, and the mixture was stirred. Next, 0.16 parts of a 25% aqueous ammonia solution was added, and the mixture was stirred. Further, dilution water was added to adjust the solid content concentration to 20%, and the coating liquid for the water vapor barrier layer was prepared. The coating liquid for the gas barrier layer and the coating liquid for the protective layer other than the coating liquid for the water vapor barrier layer were the same as those in Example 1.
[0088] The coating amount of the water vapor barrier layer coating solution (after drying) is 6 g / m 2 The coating amount (after drying) of the gas barrier layer coating solution on the water vapor barrier layer was 3.0 g / m 2 Furthermore, the coating amount (after drying) of the protective layer coating solution on the gas barrier layer was 3.0 g / m 2 Three layers were simultaneously coated on a bleached kraft paper so that the thickness of the coating was 300 μm. A multi-layer slide curtain coater for experiments was used for the simultaneous coating. After that, the product was dried at 120°C for 3 minutes in a hot air dryer to obtain a barrier laminate.
[0089] Example 6 A barrier laminate was obtained in the same manner as in Example 5, except that the protective layer coating liquid was changed to a self-emulsifying ethylene-acrylic acid copolymer emulsion.
[0090] Example 7 34.3 parts of self-emulsifying ethylene-acrylic acid copolymer emulsion was added to 19.7 parts of an aqueous dispersion of synthetic mica while stirring, and the mixture was stirred. 1.7 parts of modified polyamide resin was added to the mixture, and the mixture was stirred. Next, 0.1 parts of 25% aqueous ammonia solution was added, and the mixture was stirred. Further, dilution water was added to make the solids concentration 20%, and the coating liquid for the water vapor barrier layer was prepared. In addition, an aqueous solution of modified polyvinyl alcohol with a solids concentration of 10% was prepared, and the coating liquid for the gas barrier layer was prepared. In addition, an aqueous solution of modified polyvinyl alcohol with a solids concentration of 10% was prepared, and the coating liquid for the protective layer was prepared.
[0091] The coating amount of the water vapor barrier layer coating solution (after drying) is 6 g / m 2 The coating was applied to bleached kraft paper using a Mayer bar so that the coating amount (after drying) of the gas barrier layer coating solution on the water vapor barrier layer was 3.0 g / m2. 2 After coating with a Mayer bar so that the coating amount of the protective layer coating solution on the gas barrier layer (after drying) was 3.0 g / m, the coating was dried at 120°C for 1 minute in a hot air dryer to form a gas barrier layer. 2 After coating with a Mayer bar so as to obtain a coating composition as shown below, the coating composition was dried in a hot air dryer at 120° C. for 1 minute to form a protective layer, thereby obtaining a barrier laminate.
[0092] Example 8 To 100 parts of a 10% solids aqueous solution of modified polyvinyl alcohol, 16.5 parts of an aqueous dispersion of synthetic mica was added, and then 26 parts of a 50% aqueous dispersion of kaolin was added to obtain a coating liquid for a gas barrier layer. A barrier laminate was obtained in the same manner as in Example 1, except that the coating liquid for the gas barrier layer was changed to this coating liquid for the gas barrier layer.
[0093] Comparative Example 1 A barrier laminate was obtained in the same manner as in Example 1, except that no protective layer was formed.
[0094] Comparative Example 2 A barrier laminate was obtained in the same manner as in Example 1, except that no modified polyamide resin was added to the water vapor barrier layer.
[0095] Comparative Example 3 A barrier laminate was obtained in the same manner as in Example 7, except that a protective layer was not formed, and that the coating fluid for water vapor barrier layer of Example 5 was used as the coating fluid for water vapor barrier layer.
[0096] The obtained barrier laminates (Examples 1 to 7 and Comparative Examples 1 to 3) were evaluated for water vapor barrier properties (water vapor permeability) and gas barrier properties (oxygen permeability). The evaluation methods for each item are as follows.
[0097] <Water vapor permeability> The measurements were taken with the barrier layer facing inward according to JIS Z 0208:1976 (cup method) B method (40°C ± 0.5°C, 90% ± 2% RH). The sample was also folded in four so that the paper base material was facing inward, and the same measurements were taken after creating a cross crease. The standard for water vapor permeability is 20g / ( m 2 · day) If the thickness was below this range, it was determined that the film was practical to use as a water vapor barrier layer.
[0098] <Oxygen permeability> The oxygen permeability was measured using an oxygen permeability measuring device (MOCON, OX-TRAN2 / 20) at 23°C and 50% RH. The standard for oxygen permeability is 10cc / m 2 It was determined that a gas barrier layer with a thermal conductivity of 1000 ppm or less was practical for use as a gas barrier layer.
[0099] The evaluation results for the barrier laminates of Examples 1 to 7 and Comparative Examples 1 to 3 are shown in Table 1. Examples 1, 4, 5, 7 and 8 correspond to reference examples.
[0100] [Table 1]
[0101] As is clear from Table 1, all of the barrier laminates of Examples 1 to 8 were excellent in water vapor barrier property and gas barrier property. Furthermore, no significant decrease in water vapor barrier property and gas barrier property was observed due to the cross folding. On the other hand, the barrier laminates of Comparative Examples 1 and 3 did not have a protective layer, and therefore the gas barrier property (oxygen permeability) significantly decreased due to the cross folding. The barrier laminate of Comparative Example 2 did not contain a cationic resin in the water vapor barrier layer, and therefore had poor water vapor barrier property. [Explanation of symbols]
[0102] 1 Paper base material 2. Water Vapor Barrier Layer 3 Gas barrier layer 4A, 4B protective layer 10, 20 Barrier laminate
Claims
1. A barrier laminate having a water vapor barrier layer, a gas barrier layer and a protective layer in this order on at least one surface of a paper substrate, the water vapor barrier layer contains a water-suspendable polymer, a layered inorganic compound, and a cationic resin, the cationic resin having a surface charge of 0.1 meq / g or more and 10 meq / g or less; the content of the layered inorganic compound in the water vapor barrier layer is 7 parts by mass or more and 20 parts by mass or less relative to 100 parts by mass of the water-suspendable polymer, The gas barrier layer contains a water-soluble polymer, 1. A barrier laminate, wherein the protective layer contains a water-dispersible polymer.
2. 2. The barrier laminate according to claim 1, wherein the surface charge of the cationic resin is from 0.1 meq / g to 5.0 meq / g.
3. Water vapor permeability is 20g / (m 2 ·day) or less, and the oxygen permeability is 10cc / (m 2 3. The barrier laminate according to claim 1, wherein the thermal expansion coefficient is 1.0-1.0×day·atm or less.
4. Water vapor permeability is 10g / (m 2 · day) and the oxygen permeability is less than 10 cc / (m 2 4. The barrier laminate according to claim 1, wherein the thermal expansion coefficient is 1.0-1.0×100 MPa (1.0-1.0 MPa) or less.
5. 5. The barrier laminate according to claim 1, wherein the water vapor barrier layer, the gas barrier layer and the protective layer are simultaneously multi-coated layers.
6. 6. The barrier laminate according to claim 1, wherein the water-soluble polymer is polyvinyl alcohol or modified polyvinyl alcohol.
7. 7. The barrier laminate according to claim 1, wherein the water-dispersible polymer contains at least one of an ethylene-acrylic copolymer, a styrene-butadiene copolymer, a styrene-acrylic copolymer, and a biodegradable resin.
8. 8. The barrier laminate according to claim 7, wherein the biodegradable resin is at least one of polybutylene succinate, polybutylene succinate adipate, polylactic acid, polybutylene adipate terephthalate, and a 3-hydroxybutanoic acid / 3-hydroxyhexanoic acid copolymer.
9. 9. The barrier laminate according to claim 1, wherein the layered inorganic compound has an aspect ratio of 80 or more and a thickness of 120 nm or less.
10. 10. The barrier laminate according to claim 1, wherein the layered inorganic compound is at least one selected from the group consisting of mica, bentonite, kaolin and talc.
11. The barrier laminate according to any one of claims 1 to 10, wherein the cationic resin is at least one selected from the group consisting of polyamines, modified polyamides, modified polyamidoamines, polyamide epichlorohydrin, and polyethyleneimines.
12. A barrier laminate described in any one of claims 1 to 11, wherein the thickness of the protective layer is 0.5 μm or more and 5 μm or less.
13. The paper base material has a basis weight of 20 g / m 2 or more and 500 g / m 2 and the density is 0.5 g / cm 3 or more and 1.2 g / cm 3 The barrier laminate according to any one of claims 1 to 12, having an Oken smoothness of 5 seconds or more.
14. A method for producing the barrier laminate according to any one of claims 1 to 13, comprising the steps of: A method for producing a barrier laminate, comprising forming the water vapor barrier layer, the gas barrier layer and the protective layer by a simultaneous multi-layer coating method.
15. The method for producing a barrier laminate according to claim 14, wherein the coating method of the simultaneous multi-layer coating method is a simultaneous multi-layer slide curtain method or a simultaneous multi-layer slide bead method.
Citation Information
Patent Citations
Filter type dust collector
JP1978031265A
Moistureproof laminate
JP2001172898A
Method of manufacturing multilayer coated support improved in barrier properties
JP2004148307A
Moisture-proof laminate
JP2004218130A
Packaging vessel for powder detergent
JP2009143615A